Crossbreeding for dairy production in the lowland tropics of Kenya. II. Prediction of performance of alternative crossbreeding strategies - Kahi, A.K.; Nitter, G.; Thorpe, W.R.; Gall, C.F. (Elsevier, 2000)
The predicted performance of nine crossbreeding strategies for milk production and reproductive traits and cow live weights (LW) were compared. The strategies were selected because of their superiority to many others. The data were from crosses of Ayrshire (A), Brown Swiss (B), Friesian (F) and Sahiwal (S) cattle. Performances were predicted from the results of a genetic model based on additive breed differences, dominance and additive X additive interaction effects for the breeds involved. The crossbreeding strategies were: first cross (F X S), two-breed rotation (AS) Rot, three-breed rotation (BFS) Rot and two- (F and S), three- (B, F and S) and four-breed synthetic breeds based on equal and unequal contribution of the foundation breeds. The mean lactation milk yield (MY) of production systems based on F X S, (AS) Rot or (BFS) Rot cows and in which replacements are raised from within, was also predicted under varying number of calvings (NL) and reproductive performance (RP). At the individual cow level, differences in the predicted MY between the F X cross, three-breed rotation and the synthetic breeds were small. While the F X S cross was superior to the two-breed rotation for predicted MY, its performance was similar for MY expressed per unit of metabolic weight. Among the synthetic breeds, differences in MY expressed per unit metabolic weight were small. At the production system level, it was predicted that MY for production systems based on F X S cows become superior to those based on (AS) Rot cows only at a NL higher than 4 and were inferior to those based on (BFS) Rot. This study shows that F X S cows were closely rivalled by the (BFS) Rot and the synthetics. Its inferiority was particularly shown at the production system level. It is concluded that the first cross is not generally the best suited for dairy production systems in the tropics. There is the need to promote greater awareness of the potential of synthetic breeds and to formulate strategies for developing and exploiting them.